(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The article reveals the contribution of the great thinker Abdurrahman Jami to the formation and development of medieval philosophical, socio-political ideas based on the scientific research of Y.E.Bertels. At the same time, the scientist’s scientific and philosophical views are discussed. Jami’s religious-mystical and educational views, their place and importance in social life are revealed